2019
DOI: 10.1007/s13280-019-01230-w
|View full text |Cite
|
Sign up to set email alerts
|

Can school children influence adults’ behavior toward jaguars? Evidence of intergenerational learning in education for conservation

Abstract: A school-based experiment was conducted in the Brazilian Amazon to examine the effects of passively received information versus active elaboration on the 'perceptions' of jaguars (Panthera onca) among students, and the effects of information communicated via illustrated book on those perceptions among student's parents. Books distributed via school decreased fathers' perceptions of social acceptance of jaguar killing, but the same books distributed via a conservation organization did not. This suggests that fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…This finding is significant to conservation because social norms can be changed. For example, conservation efforts targeting well-respected individuals or institutions in a community can influence the social acceptability of specific behaviors (Veríssimo, 2013;Veríssimo and McKinley, 2016;Jones et al, 2019;Marchini and Macdonald, 2019). Furthermore, measurements of conservation success may need to include levels of persecution, rather than solely attitudes and beliefs, even though the behavior can be a more sensitive topic given legal regulations and potential consequences.…”
Section: Future Jaguar Conservation Strategiesmentioning
confidence: 99%
“…This finding is significant to conservation because social norms can be changed. For example, conservation efforts targeting well-respected individuals or institutions in a community can influence the social acceptability of specific behaviors (Veríssimo, 2013;Veríssimo and McKinley, 2016;Jones et al, 2019;Marchini and Macdonald, 2019). Furthermore, measurements of conservation success may need to include levels of persecution, rather than solely attitudes and beliefs, even though the behavior can be a more sensitive topic given legal regulations and potential consequences.…”
Section: Future Jaguar Conservation Strategiesmentioning
confidence: 99%
“…This suggests that shifting attitudes through awareness and education, taking advantage of the already strong cultural and symbolic meaning of jaguars in these communities, may be an effective way to address these behaviours, as shown by other studies (e.g. Engel et al, 2017;Marchini and Macdonald, 2020). However, the simultaneous existence of commercial and non-commercial interests behind the jaguar trade, and of domestic and foreign markets, means that further efforts should also focus on understanding market dynamics.…”
Section: Discussionmentioning
confidence: 83%
“…This concept of children as agents of change for family health has been seen and applied in a broad range of health-related community interventions [76]. Although studies relating have been limited with mixed results, this concept has been shown to be positive in educating and influencing behaviour change in parents [76][77][78].…”
Section: Discussionmentioning
confidence: 99%